Education of CA Technologies in Mechanical Engineering Study - Viera Poppeova; Nadezda Cubonova; Juraj Uricek (Communications - Scientific letters of the University of Zilina, 1999)
Process of education in study branch Production Systems Equipped with Robots and Manipulators is mainly oriented towards the areas of Numerically Controlled Machines and Computer Aided Technologies, Computer Aided Design and Computer Aided Manufacturing Systems in Mechanical Engineering.